THE USE OF SIM TO IMPROVE STUDENTS’ MOTIVATION OF MATHEMATICS LEARNING SIM (STUDY INSTAGRAM MATHEMATICS) - Risda Intan Sistyawati; Arika Sari; Somakim Somakim (Sriwijaya University Learning and Education International Conference, 2018)
The development of technology is increasing rapidly. In this case, the development of technology has its own pros and cons for the people, especially in education. Therefore, the purpose of this paper are firstly to prove that social media, which one of them is Instagram, can be an alternative for the enhancement of student motivation especially in mathematics lesson and secondly to know other functions of social media nowadays. With the development of the current era, SIM (Study Instagram Mathematics) is one of the social-media-based learning, especially Instagram, by utilizing various existing features to support the means of media for interactive learning media. During this time most people know that social media can cause negative impact as it declinelearning motivation. But actually, otherwise, social media have benefits for life, especially in the implementation of education. In this case, one of the social media, Instagram, can be used as one of the learning media that can increase student motivation. One way to improve students' motivation in learning mathematics, for now, is through the existence of an account of interesting and useful social media in the dissemination of positive information about learning, one of which mathematics learning through SIM (Study Instagram Mathematics).